Peran Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (Bhabinkantibmas) Kepolisian Sektor Yendidori dalam Penanganan Tindak Pidana Ringan - Zasima Margawaty Djamil (Kyadiren, 2020)
This study aims to determine the process of handling minor crimes carried out by Bhayangkara Community Security and Order Trustees (Bhabinkamtibmas )of the National Police, so that from this process it can be seen the extent of the role of Bhabinkamtibmas in handling minor crimes in the Yendidori District, and to find out the obstacles faced by the National Police Bhabinkamtibmas in handling minor crimes in the district. Yendidiori District. The approach used in this research is sociological juridical research. Data collection techniques used are literature studies and field studies (interviews and observations). The results of the study indicate that the Yendidori National Police acts as a mediator and facilitator in every problem that exists in their area of ​​responsibility. If minor crimes are resolved by Bhabinkamtibmas, the state budget for investigation can save billions of rupiah. In the implementation of problem solving activities, there are several obstacles faced by Bhabinkamtibmas, including the influence of the problematic party or third person during the mediation process, the community does not understand the applicable laws and regulations, and Bhabinkamtibmas still does not understand the technique of problem solving, especially administrative problems.